STUDI KOMPARASI ANTARA MADZHAB HANAFI DAN MAZHAB SYAFI’I TENTANG PENGGUNAAN LAFADZ IJAB QABUL DALAM PERKAWINAN - Moh. Ahmadi (Indonesian Journal of Islamic Law, 2019)
Islam was intented to do good to the rest of the world and spare them from the destruction. One of God’s instruction in Islam is His command to marry and His condemn to adultery. The order of marriage is one of implementation under the five rules of maqashid asy-Syariah of the maintaining of the descent. In a marriage, ijab qabul is very important due to the whole Madzhab agrees to it as the marriage arrangement. In addition, ijab qabul is the door of the house hold ark that the husband and his wife will take in. Due to of the importance of ijab qabul, thus the majority of the Madzhab explained the matters connected with it with argument included the problem with the legitimate use of lafadz used in it. One Madzhab was Hanafi and Syafi’i. This research uses literature by doing study on written sources. This is qualitative. And the analytic method is an analytic description. The conclusion from this is there are several similarities and differences between Hanafi and Syafi’i. The equation were those two sharih words (a lafadz that definitely refers to the word marriage) which is the word comes from nakaha and zawaja. Whereas the distinction is the legitimate of the non-sharih lafadz (a lafadz does not refers to the word marriage). Hanafi considered less humanist due to using a lack respect word for future wife. Whereas Syafi’i considered humanist madzhab due to using the lafadz does not disparate the future wife.